2019
DOI: 10.1177/1932296819831042
|View full text |Cite
|
Sign up to set email alerts
|

State of the Science: A Scoping Review and Gap Analysis of Diabetes Online Communities

Abstract: Diabetes is a complex chronic condition that requires ongoing self-management. People with diabetes (PWD) and their caregivers (ie, parent) spend less than 1% of their time in a year visiting with their diabetes health care provider (HCP). 1,2 As a result, PWD and their caregivers troubleshoot day-today activities on their own. It is estimated PWD spend 8000 hours per year self-managing their diabetes outside of the medical setting. 1 The Diabetes, Attitudes, Wishes and Needs Second Study (DAWN2) suggests PWD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 82 publications
(255 reference statements)
5
101
0
Order By: Relevance
“…Reduction in A1C, diastolic blood pressure, and weight provided the strongest clinical evidence for peer support in both in-person and technology-mediated environments. Recent additional studies not examined in this review of reviews corroborate our findings, [22][23][24] providing additional evidence of A1C benefits related to peer support. Specifically related to online peer support, Litchman et al 24 found that A1C was neutral among adolescents and children whose parents used online peer support.…”
Section: Clinical Outcomessupporting
confidence: 84%
“…Reduction in A1C, diastolic blood pressure, and weight provided the strongest clinical evidence for peer support in both in-person and technology-mediated environments. Recent additional studies not examined in this review of reviews corroborate our findings, [22][23][24] providing additional evidence of A1C benefits related to peer support. Specifically related to online peer support, Litchman et al 24 found that A1C was neutral among adolescents and children whose parents used online peer support.…”
Section: Clinical Outcomessupporting
confidence: 84%
“…However, this would not fully exclude representation of Asperger’s-related content as it is an ASD, and it would also tend to skew the sample toward more severe levels of impairment, increasing the ability to identify challenges within the sample. This study aligns with previous work involving the DOC that demonstrates a larger web presence of white individuals living in suburban or urban areas, which is not likely representative of the greater population with comorbid T1D and ASD [ 36 ]. This may represent a health disparity whereby those in rural areas or from diverse ethnic backgrounds may not be aware of the DOC, may not have access, or may not feel welcome or included in that space.…”
Section: Discussionsupporting
confidence: 88%
“…Although there have been documented benefits to DOC use [7,41,42], baby boomers, in particular, may experience other benefits not yet explored. Research indicates isolation and loneliness is an increasing concern in older adult populations [43,44].…”
Section: Discussionmentioning
confidence: 99%